Cable health degradation III - water tree effect on cables insulation - Htet Thinzar Tun (Nanyang Technological University, 2022)
Singapore distribution system, underground cables are utilized rather than overhead lines due to lack of land. As more underground cables are developed, it is extremely important to determine these cables' health. Water-Trees are one of the most common causes of cable health degradation and occur when the cable’s insulation dielectric breaks down. Electrical tension between the insulation and conductors of the cables leads them to develop. The proposed dissertation studies the growth of water-tree in underground cables and methods for detecting water-tree locations and the effect of water tree length and the area in which the current flows in the insulation using MATLAB/Simulink water tree model simulation. The simulation results for different water tree lengths of 100μm, 200μm, 400μm and 500μm reveal that the current flowing through that water tree area increases as the water tree strength grows indicating the presence of water tree and severity of water tree.